In Vivo Clonal Analysis Reveals Random Monoallelic Expression in Lymphocytes That Traces Back to Hematopoietic Stem Cells - Kubasova, Nadiya; Alves-Pereira, Clara F.; Gupta, Saumya; Vinogradova, Svetlana; Gimelbrant, Alexander; Barreto, Vasco M. (Frontiers in Cell and Developmental Biology, 2022)
Evaluating the epigenetic landscape in the stem cell compartment at the single-cell level is essential to assess their heterogeneity and predict their fate. Here we evaluated the allelic expression imbalance, as a read-out of epigenetic marking, in the progeny of single hematopoietic stem cells (HSC) in vivo, by a genome-wide transcriptomics approach. After four months of extensive proliferation and differentiation, we found that X-chromosome inactivation (XCI) is tightly maintained in all single-HSC derived hematopoietic cells. In contrast, the vast majority of the autosomal genes did not show clonal patterns of random monoallelic expression (RME). However, a persistent allele-specific autosomal transcription in HSC and their progeny was found in a rare number of cases, none of which has been previously reported. These data show that: 1) XCI and RME in the autosomal chromosomes are driven by different mechanisms; 2) the high frequency of genes (up to 15%) under RME in clones expanded in vitro, previously reported, is not found in clones undergoing multiple differentiation steps in vivo; 3) prior to differentiation, HSCs have stable patterns of autosomal RME. We propose that most RME patterns in autosomal chromosomes are erased and established de novo during cell lineage differentiation.